Climato-Economic Context of Regional Crime and Corruption Across the Russian Federation. Issue 3 (April 2022) - Tatarko, Alexander N.; Maklasova, Ekaterina V.; Van de Vliert, Evert
Cross-national research claims that the crime-and-corruption gap between relatively poor and relatively rich countries is larger in more demanding climates that require more cash and capital to cope with the climate. However, this claim is premature because countries differ in many confounding ways including histories and politics. We, therefore, re-tested the climato-economic context of violent crime and corruption within Russia, a country with considerable regional differences in climate and income. Across the eighty-five administrative units of Russia, the crime-and-corruption gap between relatively poor and relatively rich regions is smaller in more demanding climates. Harsher climates are so strongly associated with higher crime levels that the potential influence of differences in wealth becomes negligible. Furthermore, harsher climates are so strongly associated with higher corruption rates in poorer regions but lower corruption rates in richer regions that the potential influence of the climatic demands as such becomes negligible.